INDIGENOUS VOICES, ANCESTRAL KNOWLEDGE: A UNIVERSITY FESTIVAL AS A PLATFORM FOR INTERCULTURAL DIALOGUE - Cervera, Maria Christina da Silva Firmino (Seven Editora, 2025)
The ongoing project, Indigenous Cultural Festival at the University: Roots and Land aims to promote the appreciation and preservation of indigenous cultural diversity, integrating academic experiences of indigenous and non-indigenous students with the cultural expressions of some indigenous communities in southeastern Pará. With objectives such as celebrating cultural manifestations, raising awareness about the contributions of indigenous peoples, promoting intercultural actions and aligning with SDGs (Sustainable Development Goals – UN) 4 and 10, the initiative highlights the importance of inclusion and intercultural dialogue in the university environment. In an Amazonian context, where indigenous identities play a central role in cultural plurality. The festival reinforces the transformative role of education in building a more equitable and sustainable society. The proposal also highlights the public university’s commitment to social responsibility, inclusion and justice, aligning with the global goals of the 2030 Agenda. Thus, the festival consolidates itself as a practice that celebrates cultural richness while promoting social and academic transformation. DOI: https://doi.org/10.56238/sevened2024.037-214